Dietary quercetin improves growth performance and modulates non-specific immunity, antioxidant capacity, and lipid metabolism via NF-κB, Nrf2, and AMPK signaling pathways in black carp (Mylopharyngodon piceus) fed high-fat diets - Jianhua Ming; Jinglong Chen; Fangjie Zheng; Ting Wang; Youhai Du; Jiahui Wang; Xianping Shao; Xia Yang; Chenglong Wu; Jinyun Ye (Aquaculture Reports)
This study explored how quercetin affected growth, innate immunity, antioxidant capacity, and lipid metabolism via NF-κB, Nrf2, and AMPK signaling molecules in juvenile black carp fed high-fat diets (HFDs). A total of 540 healthy fish (10.53 ± 0.35 g) were randomly divided into 6 groups with 3 replicates each and fed a normal-fat diet with 5 % fat (NFD), a HFD with 15 % fat, and 4 HFDs supplemented with quercetin at different doses for 8 weeks, respectively. The results revealed that, compared to the NFD group, the HFD group significantly reduced growth and immune parameters (P < 0.05), leading to inflammatory response, oxidative stress, lipid metabolism disorder, and hepatic histopathological symptoms. However, compared to the HFD group, 1) Supplementing 600 mg/kg quercetin in HFD increased WGR, SGR, and SR, while reducing FCR (P < 0.05); 2) HFD supplemented with 600 and 900 mg/kg quercetin improved hepatic histopathological abnormalities, enhanced serum lysozyme, ACP, and ALP activities, and upregulated mRNA expression levels of liver immune genes and anti-inflammatory cytokines, while downregulating pro-inflammatory cytokines mRNA expression (P < 0.05); 3) Adding 600 and 900 mg/kg quercetin to HFDs boosted liver antioxidant enzyme activities and upregulated mRNA expression levels of these antioxidant enzymes and nrf2, while inhibiting keap1a and keap1b mRNA levels (P < 0.05); 4) Supplementing 600 and 900 mg/kg quercetin in HFDs reduced serum lipid content and upregulated mRNA expression levels of AMPK subunits and lipolysis genes, while downregulating mRNA expression levels of lipogenesis genes in the liver of black carp (P < 0.05). Therefore, supplementing quercetin at 600 and 900 mg/kg in HFDs improved growth, enhanced immunity and antioxidant capacity, promoted lipid metabolism, alleviated inflammatory response and oxidative stress damage in fish by inhibiting NF-κB or activating Nrf2 and AMPK signaling pathways. Based on binomial regression analysis of WGR, the optimal quercetin supplemental level in high-fat diets for juvenile black carp was 620.50 mg/kg.